Disruption and Incommensurability Among Thomas S. Kuhn’s Paradigms - Anas, Mohamad (KALAM, 2021)
This paper specifically looks at the implications of Thomas S. Kuhn's ideas regarding the distinction between context of justification and context of discovery in the emergence of science. Kuhn's thesis is that science is not only formed from the context of justification, but the context of discovery (history) must also be considered. The method of research is an in-depth interpretation towards the relevance text to the research and then the author applies analytical method to examine certain terms objectively. The author also applies historical method to see the historical aspects of a thought and finally applies the heuristic method to obtain the novelty of a work. The results of the study indicate that by considering the context of invention of science, Kuhn is in fact trapped in an epistemological relativism. Kuhn's main weakness is the absolute and extreme discontinuity among competing paradigms due to his main idea of the incommensurability paradigm, that is, it is impossible to compare one paradigm to another. In this short article the author mutually analyses Kuhn's ideas with critical method. Finally, the author notes that special nature of such paradigms socially and culturally does not create a relative gap necessarily. However, it should be a capital of conversation and dialogue across cultures and civilizations.